1988
DOI: 10.1128/mcb.8.1.301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a common ecotropic viral integration site, Evi-1, in the DNA of AKXD murine myeloid tumors.

Abstract: AKXD-23 recombinant inbred mice develop myeloid tumors at a high frequency, unlike other AKXD recombinant inbred strains which develop B-cell lymphomas, T-cell lymphomas, or both. AKXD-23 myeloid tumors are monoclonal, and their DNA contains somatically acquired proviruses, suggesting that they are retrovirally induced. We identified a common site of ecotropic proviral integration that is present in the DNA of all AKXD-23 myeloid tumors that were analyzed and in the DNA of all myeloid tumors that occur in AKXD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
128
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(130 citation statements)
references
References 41 publications
1
128
1
Order By: Relevance
“…The ten zinc finger motifs of EVI1 are grouped in a proximal domain containing 7 motifs and a distal domain of 3. EVI1 was first identified as a preferential integration site of ecotropic retroviruses in the MDS1/EVI1 genomic locus in susceptible mice leading to myeloid tumors [2]. This complex genomic locus spans over 600 kb and normally leads to the expression of at least two proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The ten zinc finger motifs of EVI1 are grouped in a proximal domain containing 7 motifs and a distal domain of 3. EVI1 was first identified as a preferential integration site of ecotropic retroviruses in the MDS1/EVI1 genomic locus in susceptible mice leading to myeloid tumors [2]. This complex genomic locus spans over 600 kb and normally leads to the expression of at least two proteins.…”
Section: Introductionmentioning
confidence: 99%
“…2 The Evi1 locus was later mapped to murine chromosome 3. 3 In addition, analysis of Cas-Br-E MuLV integration sites showed that integration at the Evi1 locus induced myeloid leukemia in NIH/Swiss and NSF mice. 1,3,4 Retroviral insertions into the murine Evi1 locus occur almost exclusively in two well-defined regions upstream of the gene, and result in the inappropriate expression of Evi1 through promoter activation by the retroviral long terminal repeat (LTR).…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, analysis of Cas-Br-E MuLV integration sites showed that integration at the Evi1 locus induced myeloid leukemia in NIH/Swiss and NSF mice. 1,3,4 Retroviral insertions into the murine Evi1 locus occur almost exclusively in two well-defined regions upstream of the gene, and result in the inappropriate expression of Evi1 through promoter activation by the retroviral long terminal repeat (LTR). 2 The preferential integration site closest to the coding region of the gene is either within a 2 kb stretch of DNA which encompasses exon 1 of Evi1, or between noncoding exons 1 and 2 of the gene, 2 and it was suggested that Evi1 transcription could be initiated from the retroviral promoter inserted into this region.…”
Section: Introductionmentioning
confidence: 99%
“…Promoter insertions of the MLV provirus responsible for gene activation have been found in, for example, the LCK, N-Ras and E2a genes (Voronova et al, 1987;Martin-Hernandez et al, 2001;Mikkers et al, 2002a, b). Perhaps more importantly, retroviral promoter insertions have been instrumental in the identification of Evi-1 (for ecotropic viral insertion site 1) as a potential oncogene both in mice and in humans ( Figure 4) (Morishita et al, 1988;Mucenski et al, 1988;reviewed in Hirai et al, 2001). Evi-1 can act both as a positive and negative regulator of gene expression, however, so far, its function is not completely understood.…”
Section: Promoter Insertions In the Oncogene Evi-1mentioning
confidence: 99%